1959
DOI: 10.1099/00221287-20-3-670
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Non-Lethal Deflagellation on Bacterial Motility and Observations on Flagellar Regeneration

Abstract: The flagellation and motility of Salmonella typhimurium were unaffected by proteolytic enzymes ; but when washed stationary-phase bacteria were briefly exposed to acid (e.g. pH 2.6 for 30 sec. at 43") the proportion of motile, and of flagellated, bacteria was decreased from more than 50 yo to less than 1 yo, with little or no decrease in viable count. When S. typhimurium or Vibrio metchnikowi grown on stiff agar were rubbed for several minutes on the agar, the proportion of motile and of flagellated bacteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1962
1962
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…The stage of differentiation in a plate culture could be determined quickly by focusing on the surface of growth derived from the sparsely inoculated plate. Motility, whether rotational, translational or absent, was checked with the phase-contrast microscope in hanging-drop mounts of organisms from the plates suspended in broth (see Stocker & Campbell, 1959).…”
Section: Methodsmentioning
confidence: 99%
“…The stage of differentiation in a plate culture could be determined quickly by focusing on the surface of growth derived from the sparsely inoculated plate. Motility, whether rotational, translational or absent, was checked with the phase-contrast microscope in hanging-drop mounts of organisms from the plates suspended in broth (see Stocker & Campbell, 1959).…”
Section: Methodsmentioning
confidence: 99%
“…Differential centrifugation adapted from the procedure of Stocker & Campbell (1959) was used to isolate sheared flagella. Cultures (1 1) of R .…”
Section: J H Martin a N D D C Savagementioning
confidence: 99%
“…Exogenously added lysine is unlikely to alter the NML content of the flagellin and one possible explanation is that the cells can synthesize more flagellin in the presence of lysine. The number of flagella per bacterium does depend to a large extent on the complexity of the growth medium (Stocker & Campbell, 1959; Kerridge, 1959) and in a minimal medium the rate of lysine synthesis, although sufficient to support formation of essential proteins, may possibly be limiting for the formation of the non-essential flagella. Exogenous lysine would overcome this limitation on flagella synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The methyl donor for the synthesis of NML in both bacterial flagella (Kerridge, 1963) and nuclear histone (Murray, 1964; Allfrey, Faulkner, & Mirsky, 1964) is methionine, and it was first suggested by Stocker et al (1961) that this methylation might occur after the incorporation of lysine into the protein molecule. More recently, Allfrey et al (1964) have found that, although puromycin inhibits the synthesis of protein by isolated calf thymus nuclei, this antibiotic has little or no effect on the methylation of the histone lysine.…”
Section: Introductionmentioning
confidence: 99%